2022
DOI: 10.1038/s41467-022-30648-2
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature high-precision printing of flexible wireless electronics based on MXene inks

Abstract: Wireless technologies-supported printed flexible electronics are crucial for the Internet of Things (IoTs), human-machine interaction, wearable and biomedical applications. However, the challenges to existing printing approaches remain, such as low printing precision, difficulty in conformal printing, complex ink formulations and processes. Here we present a room-temperature direct printing strategy for flexible wireless electronics, where distinct high-performance functional modules (e.g., antennas, micro-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
98
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 44 publications
0
98
1
Order By: Relevance
“…Great efforts have been made by incorporating functional fillers such as transition metal carbides and/or nitrides (MXene), graphene nanosheets, carbon nanotubes, and silver nanowires (AgNWs) into the polymer matrix. Among them, the newly emerged two-dimensional (2D) MXene with satisfactory hydrophilicity, large specific area, metallic-like conductivity, and abundant native defects has aroused widespread attention in the EMI shielding field. Meanwhile, AgNWs are widely used to construct CPCs with notable EMI SE and TC owing to their ultrahigh aspect ratio, brilliant electrical conductivity, remarkable heat transfer, and excellent mechanical characteristics. ,, The design of an asymmetrical structure could combine the advantages of individual components fully and control the distribution of functional filler in a special layer, which can eliminate the restriction of the nonadjustable reflection feature in EMI shielding materials with fixed impedance matching. In addition, the asymmetrical architecture presents versatility owing to the different chemical compositions and microscopic morphologies on two sides. , Consequently, the construction of an asymmetric layered structure may be an ideal approach to obtaining multifunctional CPCs with high-efficiency EMI SE entailing strong EMW absorption and superior thermal management capability simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been made by incorporating functional fillers such as transition metal carbides and/or nitrides (MXene), graphene nanosheets, carbon nanotubes, and silver nanowires (AgNWs) into the polymer matrix. Among them, the newly emerged two-dimensional (2D) MXene with satisfactory hydrophilicity, large specific area, metallic-like conductivity, and abundant native defects has aroused widespread attention in the EMI shielding field. Meanwhile, AgNWs are widely used to construct CPCs with notable EMI SE and TC owing to their ultrahigh aspect ratio, brilliant electrical conductivity, remarkable heat transfer, and excellent mechanical characteristics. ,, The design of an asymmetrical structure could combine the advantages of individual components fully and control the distribution of functional filler in a special layer, which can eliminate the restriction of the nonadjustable reflection feature in EMI shielding materials with fixed impedance matching. In addition, the asymmetrical architecture presents versatility owing to the different chemical compositions and microscopic morphologies on two sides. , Consequently, the construction of an asymmetric layered structure may be an ideal approach to obtaining multifunctional CPCs with high-efficiency EMI SE entailing strong EMW absorption and superior thermal management capability simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To date, Ti 3 C 2 T X is the most widely studied MXene and can be obtained by selective etching of Al elements in MAX in a mixed solution of HCl and LiF 29 . After sufficient washing and centrifugation, MXene nanosheets in the supernatant are widely used for electrodes, 30 energy storage devices, 31,32 and sensors 33,34 . The remaining sediments containing unetched MAX and unexfoliated MXene are discarded as trash, resulting in enormous waste and unnecessary costs.…”
Section: Introductionmentioning
confidence: 99%
“…29 After sufficient washing and centrifugation, MXene nanosheets in the supernatant are widely used for electrodes, 30 energy storage devices, 31,32 and sensors. 33,34 The remaining sediments containing unetched MAX and unexfoliated MXene are discarded as trash, resulting in enormous waste and unnecessary costs.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al 61 have reported a study on room-temperature high-precision printing of flexible wireless electronics based on MXene inks. They worked on a few RF sensors and tags with various applications such as strain and temperature.…”
Section: ■ Introductionmentioning
confidence: 99%